A Qualitative Study on Learning Environments and Disruption in Physical Education; [Un Estudio Cualitativo Sobre Entornos de Aprendizaje y Disrupción en la Educación Física] - Zavala-Alegria, J (Federacion Espanola de Docentes de Educacion Fisica, 2025)
Introduction: Physical Education class provides an ideal environment for teaching through movement and promoting values and standards of behavior. Objective: to identify the key factors that influence disruptive behavior in secondary school students and the responses of teaching staff to these acts during Physical Education classes. Methodology: A qualitative-phenomenological methodology based on grounded theory and an exploratory and prospective approach were used. Nine experts, selected for their suitability and experience, were interviewed in depth. Inductive analysis allowed for establishing categories and codes to systematize the accounts. Results: The results show causal factors for disruptive behavior and allow students to be characterized as most likely to engage in it. Discussion: The need for cooperative commitment is confirmed. As presented in previous research, developing responsibility at all age levels is imperative to learn how to behave in the Physical Education classroom. To this end, defining a frame of reference with agreed-upon forms of action and interrelation during the Physical Education class is necessary. Conclusions: These highlight the need to design pedagogical strategies that mitigate the consequences of disruptive behavior, considering the students context. Planning should include actions that favor an optimal learning environment, ensuring effective responses to situations that alter the class dynamics. Therefore, the role of the teacher is to create a structured environment that facilitates coexistence and the development of socio-emotional skills in the students. © 2025 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.